Should the African Union be granted a permanent seat in the United Nations Security Council? - Dyani-Mhango, Ntombizozuko (University of Pretoria, 2023)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2022.